Prediction of transient tumor enlargement using MRI tumor texture after radiosurgery on vestibular schwannoma. Issue 4 (18th February 2020) - Langenhuizen, Patrick P. J. H.; Sebregts, Sander H. P.; Zinger, Svetlana; Leenstra, Sieger; Verheul, Jeroen B.; de With, Peter H. N.
Abstract : Purpose: Vestibular schwannomas (VSs) are uncommon benign brain tumors, generally treated using Gamma Knife radiosurgery (GKRS). However, due to the possible adverse effect of transient tumor enlargement (TTE), large VS tumors are often surgically removed instead of treated radiosurgically. Since microsurgery is highly invasive and results in a significant increased risk of complications, GKRS is generally preferred. Therefore, prediction of TTE for large VS tumors can improve overall VS treatment and enable physicians to select the most optimal treatment strategy on an individual basis. Currently, there are no clinical factors known to be predictive for TTE. In this research, we aim at predicting TTE following GKRS using texture features extracted from MRI scans. Methods: We analyzed clinical data of patients with VSs treated at our Gamma Knife center. The data was collected prospectively and included patient‐ and treatment‐related characteristics and MRI scans obtained at day of treatment and at follow‐up visits, 6, 12, 24 and 36 months after treatment. The correlations of the patient‐ and treatment‐related characteristics to TTE were investigated using statistical tests. From the treatment scans, we extracted the following MRI image features: first‐order statistics, Minkowski functionals (MFs), and three‐dimensional gray‐level co‐occurrence matrices (GLCMs). These features were applied in a machine learning environment for classification of TTE, using support vector machines. Results: In a clinical data set, containing 61 patients presenting obvious non‐TTE and 38 patients presenting obvious TTE, we determined that patient‐ and treatment‐related characteristics do not show any correlation to TTE. Furthermore, first‐order statistical MRI features and MFs did not significantly show prognostic values using support vector machine classification. However, utilizing a set of 4 GLCM features, we achieved a sensitivity of 0.82 and a specificity of 0.69, showing their prognostic value of TTE. Moreover, these results increased for larger tumor volumes obtaining a sensitivity of 0.77 and a specificity of 0.89 for tumors larger than 6 cm 3 . Conclusions: The results found in this research clearly show that MRI tumor texture provides information that can be employed for predicting TTE. This can form a basis for individual VS treatment selection, further improving overall treatment results. Particularly in patients with large VSs, where the phenomenon of TTE is most relevant and our predictive model performs best, these findings can be implemented in a clinical workflow such that for each patient, the most optimal treatment strategy can be determined.